How digital technologies boost value potential creation and value realization in CE: insights from a multiple case study across industries - Rusthollkarhu, Sami (Edward Elgar Publishing, 2021)
Digital technologies have been identified as key catalysts for business model innovation, which enables the circular economy (CE). However, in the context of CE, they are mainly discussed in relation to resource efficiency, extended lifespans, and loop closing, leaving the realm of customer value creation unexplored. This chapter contributes to this topic by explicitly focusing on customer value creation as well as highlighting the aspects of value potential creation and realization. It presents the findings of a multiple case study consisting of six companies operating on CE principles. We propose four roles of digital technologies in CE customer value creation. The roles contribute to the CE literature by explaining how digital technologies enable companies and customers to create value based on CE principles. In practice, the roles help companies to understand the use of digital technologies in planning and executing CE business and help guide innovation at the managerial level.